2006
DOI: 10.1063/1.2359688
|View full text |Cite
|
Sign up to set email alerts
|

Core level and valence band photoemission spectra of Au clusters embedded in carbon

Abstract: X-ray photoelectron spectroscopy (XPS) has been applied for size estimation of Au clusters formed by ion implantation into glassy carbon. The 4f and 5d XPS spectra reveal the presence of the cluster 0.7–2.5nm in diameter, depending on the Au concentration. The relationship between XPS 4f-binding energy shift and 5d splitting is determined for the Au clusters embedded in the carbon and found to be significantly different from the previous data for the ones supported on a carbon substrate. We suppose that this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
6
15
0
Order By: Relevance
“…The survey spectrum shows signals from Au, C and N and the detailed analysis of the Au4f, C1s, N1s and Br3d core level spectra (presented in supporting information), concurs well with the data reported on Au nanoparticles and CTAB capped gold nanospheres and rods [38,39], thus confirming the formation of Au 0 species capped with CTAB. To prove that Au fibers can accept photo-generated electrons from the TiO2/CdS assembly, two control experiments were performed.…”
Section: Electron Microscopy Analysissupporting
confidence: 86%
“…The survey spectrum shows signals from Au, C and N and the detailed analysis of the Au4f, C1s, N1s and Br3d core level spectra (presented in supporting information), concurs well with the data reported on Au nanoparticles and CTAB capped gold nanospheres and rods [38,39], thus confirming the formation of Au 0 species capped with CTAB. To prove that Au fibers can accept photo-generated electrons from the TiO2/CdS assembly, two control experiments were performed.…”
Section: Electron Microscopy Analysissupporting
confidence: 86%
“…It is well known that the binding energy spectra of Au 4f of metallic gold NPs is appeared as doublet with binding energy 83.9 eV for 4f 7/2 and 87.3 for 4f 5/2 peak. 54 It was reported 55,56 by various groups that binding energy of Au 4f electron for very small gold cluster shis towards higher binding energy in compared to the position of bulk as the size of the nanoparticles is reduced. Recently Mark Turner et al reported 57 binding energy of Au 4f 7/2 electron for very small (1-2 nm) gold nanoparticles was 1.1 eV higher than that of bulk Au.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4d shows Au4f5/2 and Au4f7/2 core level peaks at 88.2, 87.3, 84.3, and 83.5 eV, all of which are slightly shifted in comparison with bulk Au probably due to the Au-BP interaction. 9,47 Figure S5 depicts the Raman scattering spectrum of the BP@Au composites. Compared to the bare BP sheets, the BP@Au composites show a larger intensity ratio of the A 1 g to B 2g mode and red-shifts of the three prominent peaks ascribed to the Au-BP interaction.…”
Section: Resultsmentioning
confidence: 99%